1997
DOI: 10.1021/jm960669+
|View full text |Cite
|
Sign up to set email alerts
|

(3R)-N-(1-(tert-Butylcarbonylmethyl)-2,3-dihydro-2-oxo-5-(2-pyridyl)-1H- 1,4-benzodiazepin-3-yl)-N‘-(3-(methylamino)phenyl)urea (YF476):  A Potent and Orally Active Gastrin/CCK-B Antagonist

Abstract: A number of new 1,4-benzodiazepin-2-one-based gastrin/CCK-B receptor antagonists related to the archetypal analogue L-365,260, and more closely to the recently reported compound YM022, have been synthesized and evaluated for biological activity. The compounds were screened for their ability to inhibit the binding of [125I]CCK-8 to gastrin/CCK-B receptors prepared from rat brains and that of [3H]L-364,718 to CCK-A receptors from rat pancreas, and were shown to be potent and selective ligands for the gastrin/CCK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 34 publications
2
48
0
Order By: Relevance
“…10) Substituted ureas 11) have also been of recent interest due to appearance of this functionality in drug candidates such as human immunodeficiency virus (HIV) protease inhibitors, [12][13][14] FKBP12 inhibitors, 15) CCKB-receptor antagonists 16,17) and endothelin antagonists. 18) Recently, Okuyama et al have reported a novel Ca 2ϩ channel blocker T-477 [(R)-(ϩ)-2-(4-chlorophenyl)-2,3-dihydro-4-diethylaminoacetyl-4H-1,4-benzothiazine hydrochloride] which prevents brain edema in rats.…”
mentioning
confidence: 99%
“…10) Substituted ureas 11) have also been of recent interest due to appearance of this functionality in drug candidates such as human immunodeficiency virus (HIV) protease inhibitors, [12][13][14] FKBP12 inhibitors, 15) CCKB-receptor antagonists 16,17) and endothelin antagonists. 18) Recently, Okuyama et al have reported a novel Ca 2ϩ channel blocker T-477 [(R)-(ϩ)-2-(4-chlorophenyl)-2,3-dihydro-4-diethylaminoacetyl-4H-1,4-benzothiazine hydrochloride] which prevents brain edema in rats.…”
mentioning
confidence: 99%
“…Separate groups of rats were pretreated subcutaneously with CCK receptor antagonists. Due to a limited supply of PD140548 and PD135158, these compounds had to be replaced by lorglumide (0.03-1 mol/kg [18] ) and YF476 (1 mol/kg [19] ) as antagonists for the CCK 1 and CCK 2 receptor, respectively. Control animals were injected subcutaneously with the vehicle, polyethylene glycol-300 (1 ml/kg).…”
Section: Methodsmentioning
confidence: 99%
“…YF-476 is a potent and orally active CCK 2 antagonist synthesized at Ferring Research Institute (Southampton, UK) [277] and co-developed with Yamanouchi Pharmaceutical Co. (Tsukuba, Japan). In vitro and vivo experiments [278,279] have confi rmed its high selectivity by showing that its affi nity for the rat brain CCK 2 receptors is 4,100 times higher than that for rat pancreatic CCK 1 receptors and that the drug is able to inhibit pentagastrinbut not histamine-stimulated acid secretion in rats and dogs.…”
Section: Gastrin (Cck 2 ) Antagonistsmentioning
confidence: 99%